Increasing Young Learners’ Vocabulary Mastery By Using English Songs - Kurnia, Cicih (LPPM Universitas Mercu Buana Yogyakarta, 2017)
Vocabulary is basic part of language when we learn english. Nowadays, introducing english vocabulary can be started in the kindergarten school. In early age, the young learners are easy to accept the language that has been given by teacher. Therefore, young learner in early age (approximately 3-4 years old) should get stimulation and learn English vocabulary in order to get preparation to study in higher level. This research was conducted to increase the young learners’ vocabulary mastery in b class of tungga dewi day-care. The classroom action research was implemented in this research. The teaching technique using songs were implemented through teaching and learning activities in two cycles of classroom action research. Each cycle of classroom action research was planning, acting, observing and reflecting. In this research, instruments to gather the data were field notes and observation checklists. Field notes and observation checklists were applied to take the data during the teaching learning process. The data would be analysed in order to solve the problems. Songs were applied in the activities of the first cycle of classrooms action research. The result of the first cycle was not quiet successful because the average of post –test score in cycle one was 37,8. Therefore, the teacher-researcher conducted the second cycle. The second cycle was conducted based on the result of the first cycle. Songs were combined the body movement in second cycle of the classroom action research. The result of the second cycle was successful because the average of post-test score was 77,78. As a conclusion, it can be concluded that the implementation of english songs could help to increase the young learner’s vocabulary mastery.